2015
DOI: 10.1007/s00270-015-1162-8
|View full text |Cite
|
Sign up to set email alerts
|

Proximal Versus Distal Splenic Artery Embolisation for Blunt Splenic Trauma: What is the Impact on Splenic Immune Function?

Abstract: Purpose To compare the impact of proximal or distal splenic artery embolisation versus that of splenectomy on splenic immune function as measured by IgM memory B cell levels. Materials and Methods Patients with splenic trauma who were treated by splenic artery embolisation (SAE) were enrolled. After 6 months splenic volume was assessed by CT, and IgM memory B cells in peripheral blood were measured and compared to a local normal reference population and to a post-splenectomy population. Results Of the 71 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 26 publications
3
22
0
Order By: Relevance
“…There was no difference between the patients with proximal and distal embolisation (7.55 (6.11–9.31) vs. 9.97 (6.75–14.74)). However, there was a significant difference between the control group and the proximally embolised group (10.75 (9.58–12.06) vs. 7.55 (6.11–9.31)); p value 0.02) [ 34 ]. Currently, a multicenter trial is being conducted (by the Davis Medical Center of the University of California) in which a total number of 90 patients will be enrolled (30 patients treated with observation, 30 with embolisation, and 30 operatively treated patients) and compared with regard to splenic function, measured by geometric mean increases in pneumococcal antibody titre [ 35 ].…”
Section: Splenic Functionmentioning
confidence: 99%
“…There was no difference between the patients with proximal and distal embolisation (7.55 (6.11–9.31) vs. 9.97 (6.75–14.74)). However, there was a significant difference between the control group and the proximally embolised group (10.75 (9.58–12.06) vs. 7.55 (6.11–9.31)); p value 0.02) [ 34 ]. Currently, a multicenter trial is being conducted (by the Davis Medical Center of the University of California) in which a total number of 90 patients will be enrolled (30 patients treated with observation, 30 with embolisation, and 30 operatively treated patients) and compared with regard to splenic function, measured by geometric mean increases in pneumococcal antibody titre [ 35 ].…”
Section: Splenic Functionmentioning
confidence: 99%
“…Quantification of IgM memory B cells may be of use for predicting an individual's capacity to mount an immune response to encapsulated bacteria following splenectomy. A large study found minimal evidence of hyposplenism following embolisation . Another study on patients with portal hypertension/cirrhosis who underwent SAE also had a significant number of patients not found to be hyposplenic …”
Section: Identifying Patients At Riskmentioning
confidence: 99%
“…A large study found minimal evidence of hyposplenism following embolisation. 16,17 Another study on patients with portal hypertension/cirrhosis who underwent SAE also had a significant number of patients not found to be hyposplenic. 18 Ultrasound and computerised tomography can be used to identify the presence of the spleen or splenic tissue, but the size of the residual tissue does not reliably correlate with function.…”
Section: Identifying Patients At Riskmentioning
confidence: 99%
“…Foley and colleagues looked specifically at B cell and B cell IgM memory and showed no statistical difference among embolization technique, with preservation of innate immunity among embolized spleens compared with splenectomy. 23 This is important given potential fatal infection outcomes associated with patients requiring splenectomies.…”
Section: Endovascular Managementmentioning
confidence: 99%